The Relationship Between Time Management and Academic Achievement Among University Students - Izzati Aufa, Nurul; Sri R, Amelia; Fatimah A, Siti; Fitriyani, Amel; Izzati Aufa, Beby Woro E (KIAN JOURNAL, 2024)
Introduction: Time management is a crucial skill for university students in balancing academic and personal responsibilities. Previous studies suggest that effective time management supports academic achievement, yet many students struggle to apply it consistently. Understanding this relationship is important to inform strategies that enhance student success. Objective: This study aimed to examine the relationship between time management skills and academic achievement among university students. Methods: A cross-sectional study was conducted at UIN Jakarta in March–April 2025, involving 39 undergraduate students. Participants completed a questionnaire assessing time management and academic performance. Data were analyzed using IBM SPSS version 29. Descriptive statistics summarized demographics, and a Chi-square test assessed the association between time management and academic achievement (p < 0.05). Results: Most students demonstrated fairly good time management (69.2%) and very good academic performance (69.2%). However, the Chi-square analysis showed no significant relationship between time management and academic achievement (p = 0.817). Conclusion: Despite previous findings suggesting a positive link, this study found no significant correlation between time management and academic success. The results highlight the complexity of academic performance and suggest that additional factors such as motivation, learning strategies, and institutional support play essential roles. These findings imply that interventions to support academic success should adopt a more holistic approach.